2012
DOI: 10.1038/nrneph.2012.279
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal syndrome: pathophysiology and potential targets for clinical management

Abstract: Combined dysfunction of the heart and the kidneys, which can be associated with haemodynamic impairment, is classically referred to as cardiorenal syndrome (CRS). Cardiac pump failure with resulting volume retention by the kidneys, once thought to be the major pathophysiologic mechanism of CRS, is now considered to be only a part of a much more complicated phenomenon. Multiple body systems may contribute to the development of this pathologic constellation in an interconnected network of events. These events in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(157 citation statements)
references
References 151 publications
2
130
0
13
Order By: Relevance
“…Cardiorenal syndrome is the complex bidirectional relationship between HF and kidney disease (45). Many mechanisms have been proposed to explain cardiorenal syndrome, including altered hemodynamics (from both poor cardiac output and venous congestion) (46), alterations in the sympathetic nervous system and the renin-angiotensin-aldosterone system, inflammation, oxidative stress, and atherosclerosis (47,48). Although we cannot determine the mechanism leading to elevations in NT-proBNP and/or TnT in our study population, it is plausible that elevations in these biomarkers reflect early changes in volume and cardiac stretch, venous congestion, subclinical atherosclerosis, or myocardial ischemia, which may contribute to decline in kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiorenal syndrome is the complex bidirectional relationship between HF and kidney disease (45). Many mechanisms have been proposed to explain cardiorenal syndrome, including altered hemodynamics (from both poor cardiac output and venous congestion) (46), alterations in the sympathetic nervous system and the renin-angiotensin-aldosterone system, inflammation, oxidative stress, and atherosclerosis (47,48). Although we cannot determine the mechanism leading to elevations in NT-proBNP and/or TnT in our study population, it is plausible that elevations in these biomarkers reflect early changes in volume and cardiac stretch, venous congestion, subclinical atherosclerosis, or myocardial ischemia, which may contribute to decline in kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…29 Already in this first publication, a relation with endothelial dysfunction was proposed. 29 Endothelial injury is implicated in CRS, 20 whereas in HFpEF patients, vascular changes represented by endothelial dysfunction have been reported. 30 A direct link between heart failure, vascular activation, metabolic comorbidities, and CKD was presented by Shestakova et al, 19 who demonstrated a correlation between endothelial dysfunction and the hallmarks of HF in CRS patients with type 1 diabetes mellitus.…”
Section: Microvascular Fibrotic Changes In Zsf1 Ob Ratsmentioning
confidence: 99%
“…15,16 Vascular oxidative stress leading to endothelial dysfunction and inflammation has been proposed as one of the key pathways in HFpEF 17 and CRS, [18][19][20] and it is strongly linked to metabolic risk factors. 19,21 However, details of the cardiac and renal microvasculature response in CRMS remain to be investigated.…”
Section: Van Dijk Et Al Vascular Response In Crms In Obese Zsf1 Ratsmentioning
confidence: 99%
“…30 Although the pathophysiology of this relationship appears to be complex, hemodynamic impairment might play a major role in CHF-induced organ dysfunctions. Mechanical circulatory support devices, such as left ventricular assist device and intra-aortic balloon pump, improve endorgan dysfunction including dysglycemia in patients with advanced CHF.…”
Section: -28mentioning
confidence: 99%